MAN AS BARBARIAN (Heritage, 2020)
Immoderate, rapid development of humanity demands immoderate exploitation of natural resources and regular environment deterioration. On the other hand, moderate consumption would mean a moderate exploitation of natural resources. Thus, instead of the consumption society should be created a safeguard one which would preserve the nature from exaggerated exploitation and pollution. In the last decades, instead of market economy the advocates of ecological or sustainable economy are appearing, and in order to preserve biosphere the industrial  economy would be replaced by the ecological one.         By the use of chemical protective or incentive agents, man deteriorated life of Divine creatures, birds, bees and other insects as the native plant pollinators. Man paradoxally polluted the air, poisoned the water, soil and plants by which he feeds himself. Almost all arable lands are poisoned by chemistry (artificial fertilizers, pesticides, herbicides). This process, instead of being slowed down is being accelerated.          As the self-proclaimed master of the planet, man is, at the same time, the greatest destroyer. In order not to be the criminal of nature in the future but its fried, man should develop a new ecological consciousness – human ecology, ethical relationship toward nature,  give up profit selfish interests, sightless exploitation, dirty and war technology and  become the one and the same with nature since the destruction and robbery of nature are one of contemporary civilization inhumanities being made by man at his own harm. Besides being barbarian against nature, man is also barbarian against his fellow-countrymen (dissidents, other believers, poor and rich ones...).  None as man is so powerful at other man harm inflict; he causes wars, revolutions, terrorism, and hate against other and own people as the ideal of world peace-making neither exists nor is desirable.
Keywords: Man, nature, destruction, extinction, causes and consequences, industrialization, ecology, the planet Earth